Empowering Digital Transformation - (:unkn) unknown (My University, 2025)
Focuses on achieving a human-centered digital transformation by empowering people and integrating processes and platforms to foster sustainable prosperity for all. It challenges conventional thinking by offering novel conceptualizations, empirical evidence, and case studies from regions at various stages of digitalization and across different product, market, and industry contexts. The book aims to equip decision-makers and academics with the tools to navigate the increasingly blurred boundaries between humans and computers, businesses, institutions, and society, and the traditional, platform, attention, and experience economies. The chapters span operations, marketing, and management and bring together a variety of country context and industries undergoing digital transformation.
Keywords: digital transformation, marketing, management